2020
DOI: 10.1038/s41598-020-73035-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the tonsillar microbiota in IgA nephropathy and other glomerular diseases

Abstract: Immunoglobulin A nephropathy (IgAN) involves repeated events of gross haematuria with concurrent upper airway infections. The mucosal immune system, especially the tonsil, is considered the initial site of inflammation, although the role of the tonsillar microbiota has not been established in IgAN. In this study, we compared the tonsillar microbiota of patients with IgAN (n = 21) and other glomerular diseases (n = 36) as well as, healthy controls (n = 23) from three medical centres in Korea. The microbiota was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…These taxonomic alterations were noted in IgAN patients when compared to healthy controls [26,31,32,34,36] or other nephropathy patients [32,33]. Some of the analyses also linked specific microbiota with remission rates [26,36] and clinical measurements, such as proteinuria [34], serum albumin [32,33], and inflammatory markers [34], thus highlighting the microbiome's potential as a diagnostic and prognostic marker of IgAN.…”
Section: Omics Datamentioning
confidence: 90%
See 2 more Smart Citations
“…These taxonomic alterations were noted in IgAN patients when compared to healthy controls [26,31,32,34,36] or other nephropathy patients [32,33]. Some of the analyses also linked specific microbiota with remission rates [26,36] and clinical measurements, such as proteinuria [34], serum albumin [32,33], and inflammatory markers [34], thus highlighting the microbiome's potential as a diagnostic and prognostic marker of IgAN.…”
Section: Omics Datamentioning
confidence: 90%
“…A sequencing-based technique targeting the bacterial 16S ribosomal RNA gene has been widely used to profile the taxonomic composition of the microbiome in different conditions. 16S analyses in IgAN reported alterations in the microbiome's structure in the saliva [31], tonsil swabs [32], and gut [33][34][35], while denaturing gradient gel electrophoresis showed compositional changes in tonsil tissues [36]. These taxonomic alterations were noted in IgAN patients when compared to healthy controls [26,31,32,34,36] or other nephropathy patients [32,33].…”
Section: Omics Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The human microbiome is closely associated with mucosal immunity, and previous findings implicated the gut, tonsil, periodontal, and salivary microbiota in IgAN (De Angelis et al, 2014;Nagasawa et al, 2014;Piccolo et al, 2015;Watanabe et al, 2017;Cao et al, 2018;Luan et al, 2019;Dong et al, 2020;Hu et al, 2020;Park et al, 2020). However, despite Japan having the second highest incidence and frequency of IgAN (Schena and Nistor, 2018), few studies have been conducted on the IgAN-associated microbiota in a Japanese cohort.…”
Section: Discussionmentioning
confidence: 99%
“…A transgenic murine model of IgAN highlighted the essential dependence of signals from the commensal microbiota for kidney IgA deposition in the pathogenesis of IgAN ( McCarthy et al , 2011 ). Few studies have reported a change in the composition of the gut ( De Angelis et al , 2014 ; Dong et al , 2020 ; Hu et al , 2020 ), salivary ( Piccolo et al , 2015 ; Luan et al , 2019 ), periodontal ( Cao et al , 2018 ), or tonsillar ( Park et al , 2020 ) microbiota in Caucasian, Chinese, and Korean IgAN patients. However, none of these studies investigated microbiome changes in IgAN versus IBD.…”
mentioning
confidence: 99%